Análise estatística multivariada e modelo geoquímico inverso no estudo da qualidade da água subterrânea da bacia de Forquilha em Quixeramobim-Ceará - Almeida, João Roberto Façanha de (2009)
The alluvial aquifers in the semi-arid region of Brazil’s Northeast host an important natural water resource for the populations that live in that region, owing to its excellent quality, when compared to the crystalline basement rock aquifers. However, they are fragile resources and are susceptible to processes of degradation of quality by anthropic action, climatic changes or hydrogeological modifications. The objective of this research is to identify and quantify the primary processes responsible for the increase in salinity observed in the alluvial aquifers during the dry season. Besides hydrochemical analysis (Piper and Stiff diagrams and ionic relations), multivariate statistical analysis (hierarchical clustering and discriminant analyses) and inverse geochemical modeling were also used. The Piper and Stiff diagrams presented water classification according to dominant ions, where the alluvial water showed intermediate characteristics between the hard-rock basement aquifer water and that from the reservoirs. With the SAR diagram, the same result was observed. The ionic relations revealed a strong relation of the alluvial water with the lithology of the region and the probable dissolution of aerosols containing composites of the MgCl2 type in the aquifers of the crystalline rock shield. Cluster analysis showed the similarities between the wells, whereas discriminant analysis helped to understand the process of salinization in the alluvial aquifer. The inverse geochemical modeling carried out with PHREEQC identified cationic exchanges of CaX2, MgX2, NaX and KX, as well as precipitation of K-mica and albite and dissolutions of anorthite and K-feldspar, evidencing the intemperic action of the water on the rocks. Strong dissolution of CO2 in the alluvial water justifies the bicarbonated characteristics of that water. The volume contribution from crystalline rock aquifer water was estimated as between 1.53% and 27.99% at different points with a mean value of 15.8%. However, this contribution represents nearly 64% of the salinity of the water in the alluvium.